Usage and adherence of antidementia drugs in a memory clinic cohort in Chongqing, Southwest China. Issue 5 (5th June 2020) - Yu, Xingyan; Yu, Weihua; Yang, Wenkai; Lü, Yang
Abstract : Background: To investigate the use and adherence of antidementia drugs in elderly patients with dementia from the Memory Clinic of The First Affiliated Hospital of Chongqing Medical University. Methods: Patients were recruited from the Memory Clinic of The First Affiliated Hospital of Chongqing Medical University from December 2010 to December 2018. Medical charts were reviewed, including diagnosis, dosage of antidementia medicines, neuropsychological testing scores, and the further questionnaires were conducted via face‐to‐face or telephone, included duration of treatment, types of antidementia drugs, and reasons for treatment discontinuation. Results: The data from 422 patients were analysed retrospectively for this study. Three hundred and fifteen were diagnosed with Alzheimer's disease (AD), 67 with mild cognitive impairment (MCI), and 40 with other types of dementia. From the 422 patients, 26.8% were treated with original donepezil (n = 113), 11.6% with generic donepezil (n = 49), 24.6% with memantine (n = 104), 13.3% with huperzine A (n = 56), and 23.7% with a combination of drugs (n = 100). However, 73% of patients discontinued treatment within 1 year of initiation. Patients treated for more than 36 months (37.8%) were more likely to choose combined medication, as compared with patients treated for less than 36 months. Patients with less than 9 years of education (odds ratio (OR): 2.394; 95% CI: 1.508–3.801) were more likely to discontinue treatment than patients with more than 9 years of education. Patients with elevated physical self‐maintenance scale (PSMS) scores (OR: 1.195; 95% CI: 1.086–1.316) had a high risk of discontinuation. Conclusions: Overall treatment compliance is relatively poor in memory clinics in Chongqing. Our study demonstrates that higher education may lead to better treatment adherence in dementia care. Combination therapy may increase treatment time. However, poorer PSMS scores are a significant risk factor for treatment discontinuation.